Focusing and Defocusing of Tropical Cyclone Generated Waves by Ocean Current Refraction. Issue 1 (18th January 2022) - Sun, Rui; Villas Bôas, Ana B.; Subramanian, Aneesh C.; Cornuelle, Bruce D.; Mazloff, Matthew R.; Miller, Arthur J.; Langodan, Sabique; Hoteit, Ibrahim
Abstract: Waves generated by tropical cyclones can have devastating effects on coastal regions. However, the role of ocean currents in modifying wave amplitudes, wavelengths, and directions is commonly overlooked in wave forecasts, despite the fact that these interactions can lead to extreme wave conditions. Here, we use satellite observations and wave modeling to quantify the effects of ocean currents on the surface waves generated during a tropical cyclone event in the Arabian Sea. As a case study, this paper documents beams of wave heights originating from the eyewall of a tropical cyclone caused by current‐induced refraction. Alternating regions of high and low wave heights in the model simulations are consistent with observations and extend for thousands of kilometers all the way to 100 m isobath. Our results highlight the importance of accounting for wave refraction by currents in order to accurately predict the impact of tropical cyclone generated waves on coastal regions. Plain Language Summary: Waves generated by tropical cyclones can have devastating effects on coastal regions. Ocean currents can modify wave heights and lead to extreme wave conditions. Here, we use satellite observations and wave modeling to quantify the effects of ocean currents on the waves during a tropical cyclone event in the Arabian Sea. In this paper, we documented the coherent beams of wave heights originating from the "center" of a tropical cyclone caused by current‐induced effects. Alternating regions of high and low wave heights in the model simulations are consistent with observations and extend for thousands of kilometers all the way to 100 m isobath. Our results highlight the importance of accounting for the currents in order to accurately predict the impact of tropical cyclone generated waves on coastal regions. Key Points: Altimeter data and WAVEWATCH III are used to quantify ocean current impacts on surface waves Coherent wave beams propagate from tropical cyclone eyewalls due to current‐induced refraction Wave height structure is dominated by background currents, and not the cyclone induced currents